Numerical methods in offshore piling proceedings of a conference organized by the Institution of Civil Engineers and held in London, 22-23 May 1979. (Institution of Civil Engineers, 1980)
This work surveys numerical methods in offshore piling, highlighting the effect of driving support conditions on pile wandering. Soil response during pile driving and the dynamic stiffness of piles is addressed.